Optimization Of Environmental Control Using Industrial Minerals For Upstream Oil And Gas Activities - Djoko Sunarjanto; Supriyatno Supriyatno; Azizah Azizah (Testing Center for Oil and Gas LEMIGAS, 2007)
Industrial minerals are useful as drilling materials support such as; limestone (MgCaCO3) for filler, bentonite and barite for drilling mud and quartz sand for propping agent. Until now the benefit of them has not been optimized because it is only as building material, and still the mining which cause environmental damage. Concerning the environmental care and to support the movement of using national products of oil and gas activities need innovations and creativities in taking the benefit of those minerals. The alternative that has been chosen such as the effort of the balancing between the national products and big investment in oil and gas. To make condition of bentonite as drilling mud was needed activation and change it to sodium bentonite to improve those mineral suspension by polymer added. Meanwhile industrial development of silica sand as gravel packing and propping agent, have been better within mining activity in Bangka Area. Average quality of silica sand consist SiO2 up of 90 % to satisfy the requirements, but still was quality improved. In few regions in Indonesia overall industrial mineral can be used to support oil and gas activities